THE RELATIONSHIP OF CLASS II ADOLESCENT GIRLS KNOWLEDGE ABOUT BREAST CANCER WITH ATTITUDES TO CONDUCT CLINICAL BREAST EXAMINATIONS (CBE) AT SMA N 8 BATAM CITY - Indah Mastikana; Febri Hartini Janet Laga; Aminah Aatinaa Adhyatma (International Journal of Social Science, 2021)
In Indonesia, the morbidity rate caused by cancer is still high. Cancer can attack all levels of society regardless of social status, age and gender. According to Mardiana (2010), it is estimated that around 60% of cancer patients are women, especially in vital organs such as the breasts and other organs such as the uterus, ovaries and vagina. Awareness of the importance of understanding what and how breast cancer is very important for early adolescents so that adolescents can detect breast cancer early, detecting breast cancer can be done at health service centers, namely through Clinical Breast Examinations (CBE). This study aims to determine the relationship between knowledge of young women about breast cancer with attitudes to perform Clinical Breast Examinations (CBE). This research is a descriptive study with a cross sectional approach, the sample was taken by accidental sampling technique with a sample of 150 people. The results of the study most of the respondents had poor knowledge about CBE examination, from the results of the Chi-square test, the p value of 0.980 was greater than the p table, which was 0.5, meaning that there was no relationship between the knowledge of young women and the attitude to carry out Clinical Breast Examinations (CBE). The conclusion from the results of the study is that the majority of good knowledge have attitudes in the strong category (30.6%), have good knowledge and have moderate attitudes (9.0%), lack knowledge and have attitudes in the strong category (6.5%), and lack of knowledge has an attitude in the medium category (13.9%).